The Relationships between Economic Growth, Energy Efficiency and CO2 Emissions: Results for the Euro Area - Klyvienė, Violeta; Kėdaitienė, Angelė (Ekonomika, 2020)
The article aims at ascertaining the relationship between indicators affecting the green economic growth of the Eurozone countries. Despite extensive research, scientists have not yet found a clear answer as to whether economic growth and climate change mitigation can be aligned. Another important aspect of the study was to investigate the possible effect of environmental policies on macroeconomic variables such as GDP, investment, employment, and trade. The authors of the article applied the PVAR econometric model to measure the impact of energy consumption, CO2 emissions, and some of the macroeconomic indicators on GDP growth in 19 countries of the Eurozone for years 2000–2016.Based on the results, we cannot yet state explicitly that economic growth in the Eurozone countries has been decoupled from climate change mitigation; however, green transition is on the right track.
Keywords: Green economic growth; GDP growth; CO2 emissions; energy efficiency; macroeconomic indicates